2021
DOI: 10.18860/iq.v17i1.7949
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Tingkat Kreativitas Wirausaha Mahasiswa Melalui Program Komunitas Entrepreneur

Abstract: This research is motivated by the Entrepreneur Community Program's existence as support for entrepreneurship courses in the Islamic Banking Department, Faculty of Economics, UIN Maulana Malik Ibrahim Malang to produce graduates who have high selling value, entrepreneurship, and creativity to be able to compete. The learning approach in the program is Project-Based Learning. This study aimed to analyze the level of student creativity before and after participating in the Entrepreneur Community Program. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The study by Paristiowati concluded that students' cooperation and communication increased through the implementation of chemo-entrepreneurship learning (Paristiowati et al, 2015) and also proved that chemo-entrepreneurship learning through project-based learning can improve students' creativity (Aisyah, 2021). Next, another study showed concluded that students' creativity was improved through the implementation of a chemoentrepreneurship oriented inquiry module (Dewi & Mashami, 2019).…”
Section: Increasinglymentioning
confidence: 99%
“…The study by Paristiowati concluded that students' cooperation and communication increased through the implementation of chemo-entrepreneurship learning (Paristiowati et al, 2015) and also proved that chemo-entrepreneurship learning through project-based learning can improve students' creativity (Aisyah, 2021). Next, another study showed concluded that students' creativity was improved through the implementation of a chemoentrepreneurship oriented inquiry module (Dewi & Mashami, 2019).…”
Section: Increasinglymentioning
confidence: 99%